Enhancing fouling mitigation of submerged flat-sheet membranes by vibrating 3D-spacers - Tan, Yong Zen (2021)
Unsteady-state shear is acknowledged to be more energy-efficient in the mitigation of membrane fouling. In this study, we aimed to understand the effects of three dimensional (3D)-spacer configuration and their vibrating orientation on the extent of fouling mitigation in a submerged flat-sheet membrane microfiltration (MF) system. Several types of 3D-spacers were designed and computational fluid dynamics (CFD) was used to simulate the shear and turbulence along the membrane surface induced by vibrating 3D-spacers. The designed 3D-spacers were produced by 3D printing technique and their fouling control efficiencies were experimentally examined in a submerged flat-sheet membrane MF system with bentonite and sodium alginate as model foulants. Both simulation and experimental results revealed that the wave-like spacer (groove direction vertical to spacer movement direction) could alleviate more membrane fouling than the other designed spacers (e.g., hill-like spacer, wave-like spacer with groove direction parallel to spacer movement direction), regardless of tested permeate fluxes. Furthermore, two types of wave-like spacers were designed based on CFD simulation, in which perforation were placed on the spacer in order to enhance shear rate and provide a path for the back transport of foulants into the bulk feed. The MF membrane tests showed that the presence of either big holes (2 mm diameter) or small holes (1 mm diameter) could not benefit to reduce membrane fouling at a lower permeate flux (20 L/m² h), but the presence of small holes significantly improved membrane performance at a higher permeate flux (40 and 60 L/m² h).